Pengembangan Media Pembelajaran Monopoli pada Pembelajaran IPA Materi Panca Indera (MONOPAN) - Rohmawati, Mely; Hidayah, Eva Resa Sirotun; Zulfa, Hana Maula; Pratiwi, Ika Ari (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to develop a monopoly-based learning medium called MONOPAN (Monopoli Panca Indera) as an effort to increase student engagement and understanding in IPAS learning of the five senses material in fourth grade elementary school. The study used the Research and Development (RD) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students at SD Negeri 4. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and learning outcome tests, then analyzed descriptively through the percentage of feasibility and learning outcome achievement. The results of validation by media, material, and language experts showed a very high level of media feasibility, with validation percentages of 97.78%, 100%, and 97.5%. In addition, the student response questionnaire showed an average score of 95.40%, indicating that the media was very feasible for use in learning. MONOPAN is proven to be able to increase motivation, active participation, and student understanding of the five senses material through a fun and interactive learning-by-play approach. The results of this study concluded that monopoly educational game-based learning media can be an innovative and effective alternative in supporting IPAS learning in elementary schools. The implications of the research show that educational media such as MONOPAN not only improve the quality of learning, but also become a suitable and practical alternative approach to create an active and fun learning atmosphere.